The effect of modafinil on the rat dopamine transporter and dopamine receptors D1–D3 paralleling cognitive enhancement in the radial arm maze - Karabacak, Yasemin; Sase, Sunetra; Aher, Yogesh D.; Sase, Ajinkya; Saroja, Sivaprakasam R.; Cicvaric, Ana; Höger, Harald; Berger, Michael; Bakulev, Vasiliy; Sitte, Harald H.; Leban, Johann; Monje, Francisco J.; et al. (Frontiers in Behavioral Neuroscience, 2015)
A series of drugs have been reported to increase memory performance modulating the dopaminergic system and herein modafinil was tested for its working memory (WM) enhancing properties. Reuptake inhibition of dopamine, serotonin (SERT) and norepinephrine (NET) by modafinil was tested. 60 male Sprague Dawley rats were divided into six groups (modafinil-treated 1-5-10 mg/kg body weight, trained and untrained and vehicle treated trained and untrained rats; daily injected intraperitoneally for a period of 10 days) and tested in a radial arm maze (RAM), a paradigm for testing spatial WM. Hippocampi were taken six hours following the last day of training and complexes containing the unphosphorylated or phosphorylated dopamine transporter (DAT-CC and pDAT-CC) and complexes containing the D1-3 dopamine receptor subunits (D1-D3-CC) were determined. Modafinil was binding to the DAT but insignificantly to SERT or NET and dopamine reuptake was blocked specifically (IC50=11.11; SERT 1547; NET 182). From day 8 (day 9 for 1 mg/kg body weight) modafinil was decreasing WM errors in the RAM significantly and remarkably at all doses tested as compared to the vehicle controls. WMEs were linked to the D2R-CC and the pDAT-CC. pDAT and D1-D3-CC levels were modulated significantly and modafinil was shown to enhance spatial WM in the rat in a well-documented paradigm at all the three doses and dopamine reuptake inhibition with subsequent modulation of D1-3-CC is proposed as a possible mechanism of action.